Seismic performance of flat slab under the different earthquake loading - Muhammad Izzulfikri, Azman (2017)
Malaysia is the country region that free from red zones which is earthquake zones. But nowadays we heard news about earthquake that suddenly happen in Malaysia. So a study of earthquake was carrying out for structural which is flat slab structure. Flat Slab Structure is the structure that will damage cause by the seismic effect and also an important structure. Most structure of Flat Slab in Malaysia does not take account the seismic loading. Therefore, by using SAP 2000 software a modal analysis was created and the purpose of this research is to study the performance of the flat slab structure. The performance characteristic includes displacement, acceleration and velocity of the flat slab structure. The performance for each member of the structure can be determined through the displacement and the acceleration value. The earthquake data is from Acheh and Bukit Tinggi earthquake that get from the Malaysia Meteorological Department. After the analyse the 12 mode shape had been shown. Each mode shape produces the different number of frequency and also natural time period. According to 12 mode shape produced, three mode shapes with the highest frequency will be selected as the best mode shape. Other than that the rigidity of shape of each mode shape also can be determined according to the classification of time period the building. The classification are Rigid (T < 0.3 sec), Semi-Rigid (0.3 sec < T < 1 sec), and Flexible Structure (T > 1).